A comparative analysis of the use of participatory practices by indigenous trusts and mainstream development NGOs in Zvimba Communal Area Zimbabwe - Mbanje, Bowden Bolt (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
This thesis compares the extent to which participatory practices have been used by Caritas Zimbabwe, a mainstream NGO, and the Zvimba Community Share Ownership Trust (ZvCSOT), an indigenous Trust, in Zvimba District, Zimbabwe. Participatory development initiatives are common practice in NGO and government development work in Zimbabwe. The thesis begins with a discussion of two aspects of participatory development (PD). Firstly, PD is discussed in relation to decentralization processes where central government transfers administrative and financial authority to sub-national government units in order to enhance the participation of rural communities in development interventions. Secondly, PD is discussed in relation to the increased role of NGOs in development work. During the 1980s and 1990s, shifts in development thinking resulted in NGOs being perceived as important actors who could attend to the development gaps left by an economically incapacitated state. Both NGOs and sub-national government units were seen to be closer to rural communities and so were thought to be in a better position to enhance the participation of these communities in meaningful development projects. An analysis of the practices of the NGO and CSOT under consideration in this study shows that while there has been much rhetorical commitment to participation, community participation in the development interventions of the NGO and the CSOT is inadequate. In introducing and implementing development interventions, there has been a tendency by both the NGO and CSOT to give priority to organizational preferences over local needs. While recognizing the participatory efforts made by mainstream development NGOs (Caritas in particular) and indigenous Trusts (Zvimba Community Share Ownership Trust in particular) in Zimbabwe, this thesis also considers the impact of other factors on participatory development initiatives. A major observation from the study is that in as much as we expect genuine participatory approaches which include grassroots communities' inputs from the project's conceptualization all the way to its evaluation, the challenge is that the elites at the higher level (central government and donor offices) have their own development preferences and interests while the elites at the lower levels (local government and NGO offices) also have their own priorities and needs. Consequently, local communities tend to be confined to implementing development projects foisted on them by elites at the higher level as well as those at the lower level. Worse still, the study shows that elites at the lowest level (community) sometimes hijack or take advantage of the imposed projects. Participation has been stalled by elites at various levels of the participatory development ladder. Thus, unless power imbalances are seriously addressed at all levels, participatory development will remain elusive.
Keywords: Caritas Zimbabwe; Zvimba Community Share Ownership Trust (ZvCSOT); Non-governmental organizations -- Zimbabwe -- Zvimba District; Community development -- Zimbabwe -- Zvimba District; Rural development -- Zimbabwe -- Zvimba District; Zvimba Communal Land (Zimbabwe)